The Right Book to Help Our Ailing Society to Recover - Kriaučiuniene, Roma (ETHICS IN PROGRESS, 2017)
This paper is a review of Georg Lind’s latest book: How to Teach Morality. Promoting Deliberation and Discussion, Reducing Violence and Deceit (2016), and focuses on the main theme of the book – morality can be taught, the idea that is most encouraging for educators. Many researchers agree that our societies face many problems, such as violence, deceit, corruption, disrespect to the human nature, which on an individual level seem to stem from the lack of moral competence. Therefore, G. Lind’s book is timely, providing answers to those who are concerned about our future. It will be of interest and great value not only for the participants of CeSPeC Summer School of 2016, who were trying to attain the inspiration for an immediate present-day action to reshape our future for the better, but to all of us who are committed to the enhancement of human existence and especially educators, who are engaged in the development of moral competence of their learners. This review is an attempt to prove to the readers that. Lind’s book How to Teach Morality. Promoting Deliberation and Discussion, Reducing Violence and Deceit, is the right book to help our ailing societies to recover.